Economic Challenges and Deficiencies in Application of Scientific Farming Practices: Barriers to Sustainable Tea Cultivation for Small Growers - Puspajit Sarkar; Dr. Tanmoy K Pal (IJRDO-Journal of Applied Science, 2024)
The Tea Board of India classifies ‘Small Growers’ as cultivators with farm size under 25 Acres in contrast to ‘large plantations’ which uses land of 25 Acres or more. Despite their smaller farm sizes, Indian small tea growers collectively produced 710 million kg of tea leaves in the 2022 season, surpassing the 656 million kg output from large plantations. This study aims to assess the significance of tea cultivation as an occupational choice for small grower households and to assess the level of adoption of scientific farming practices among small tea growers. Findings from primary data reveal that most small growers rely heavily on tea cultivation, with little or no diversification into other crops due to land scarcity and economic constraints. This study also found that small tea growers had deficiencies in understanding and application of seven critical scientific farming practices. Results of statistical tests underscore the significant influence of both landholding size and occupational status on adoption of selected scientific farming practices (soil testing, mulching, maintenance pruning of bushes, and use of organic pesticides) among small tea growers. These results highlight the need for targeted intervention strategies to improve adoption of sustainable farming practices by small growers and their economic stability.